Commodification of Dieng Gimbal hair children in digital media: norman fairclough's critical discourse analysis - Mahmudi, Marwan; Amrullah, Haekal Fajri; Iskandar, Dadan; Ramadhanti, Nabilah; Hasibuan, Marzuki; Widyastuti, (Penerbit Universiti Kebangsaan Malaysia, 2020)
The tradition of Ruwatan Hair Cutting Giembael is a ritual that has been passed down from generation to generation by the Dieng plateau community. In this tradition, there are sacred values that are still believed and affect the lives of people in the Dieng plateau. The formulation of the problem of this research was How the Commodification of Dieng dreads children's news content by digital media. This study used the Norman Fairclough critical discourse analysis instrument. Critical discourse analysis is used to scrutinize and see how the commodification of culture in three online news portals including Tempo.co, Republika Online, and Liputan6.com. Data collection techniques with documentation were used to look for coverage in digital media. The results of the research were divided into 3 analyses, namely text analysis which showed the presence of media diction utilizing dreadlocks ceremony as an economic commodity and media alignments with festival organizers. The next one was the analysis of text production that the news is produced very interestingly, the information was presented in a very full rich of oddities or myths to attract readers. Lastly, the socio-cultural analysis explained that the three news portals utilized the village community's social conditions which still strongly believed in the myths of dreadlocks' children being packaged in festival events.